2021
DOI: 10.1002/elan.202060455
|View full text |Cite
|
Sign up to set email alerts
|

Novel Zn‐Fe LDH/MWCNTs and Graphene/MWCNTs Nanocomposites Based Potentiometric Sensors for Benzydamine Determination in Biological Fluids and Real Water Samples

Abstract: Two sensitive and selective potentiometric sensors based on zinc‐iron layered double hydroxides/multiwalled carbon nanotubes (Zn−Fe LDH/MWCNTs) (sensor I) and graphene/multiwalled carbon nanotubes (Gr/MWCNTs) (sensor II) nanocomposites were developed for benzydamine hydrochloride (Benz) determination. The investigated sensors displayed excellent Nernstian slopes 58.5±0.7 and 59.5±0.5 mV decade−1, detection limits 8.3×10−7 and 1.9×10−7 mol L−1, long lifetimes, adequate selectivity, high chemical, and thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Repeatability and reproducibility are referred to the degree of agreement between the results of subsequent measurements of the same analyte, performed under specific conditions. 13 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeatability and reproducibility are referred to the degree of agreement between the results of subsequent measurements of the same analyte, performed under specific conditions. 13 …”
Section: Resultsmentioning
confidence: 99%
“…Repeatability and reproducibility are referred to the degree of agreement between the results of subsequent measurements of the same analyte, performed under specic conditions. 13 The reversibility of a sensor which is the ability of the sensor to recover, or return to its original background/baseline condition was checked by recording the sensor response in the sequence high-to-low from 1.0 × 10 −2 to 1.0 × 10 −7 mol L −1 sample concentrations of (DTZ) drug. The results showed that the response of the sensors was reversible (Fig.…”
Section: Sensor Potential Response Characteristics and Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in this case the resulting EDL has a very small capacitance, which leads to a significant drift of potentiometric response during the time [32,33]. To decide this problem, it has been proposed to disperse different Carbon Nanoparticles (CNPs) directly into the ion-sensing membrane compositions [34][35][36][37][38][39]. The functionalized nanomaterials were found to be favorable for developing such type of sensors [40][41][42].…”
Section: Introductionmentioning
confidence: 99%